Berjumpa Kemajemukan dalam Ruang Virtual: Upaya Membangun Toleransi melalui Pendidikan Kristen - Hakmoni Daud Parhusip; Yohanes Joko Saptono (Jurnal Teologi Gracia Deo, 2024)
This article investigates and describes the role of virtual space in dealing with religious pluralism in the context of Christian religious education. Considering digital technology's advanced and massive development, virtual space has become an essential platform for interfaith interaction. Both as broadcasting and spiritual formation, but the main focus is on how individuals and Christian communities use virtual space to promote tolerance and mutual respect as the basis of social life and, of course, as an understanding of various beliefs through a descriptive qualitative method with a study approach and literature review. This journal article analyzes the strategies and practices used by Christian communities in facing the challenges of religious pluralism in virtual space. The results show the importance of inclusive approaches and inter-religious dialog in building tolerance and respect amidst the challenges of a fast-paced era full of modern technological sophistication. The practical and theoretical implications of the findings are discussed, as well as recommendations for developing Christian religious education that is more adaptive to the increasingly complex realities of virtual space.  AbstrakArtikel ini menginvestigasi dan mendeskripsikan peran ruang virtual dalam menghadapi kemajemukan agama dalam konteks pendidikan agama Kristen. Menilik semakin maju dan massifnya perkembangan teknologi digital, ruang virtual menjadi platform penting bagi interaksi lintas agama. Baik sebagai siar maupun pembinaan rohani, namjun fokus utama adalah bagaimana personal maupun komunitas kekristenan menggunakan ruang virtual untuk mempromosikan toleransi dan saling menghargai sebagai dasar dari hidup bermasyarakat, tentunya hal itu sebagai pengertian di antara berbagai kepercayaan. Melalui metode kualitatif deskritif dengan pendekatan studi dan tinjauan literatur. Maka artikel jurnal ini menganalisis strategi dan praktek yang digunakan oleh komunitas Kristen dalam menghadapi tantangan kemajemukan agama dalam ruang virtual. Hasil penelitian menunjukkan pentingnya pendekatan inklusif dan dialog antar-agama dalam membangun toleransi dan bentyuk menghargai yang kokoh di tengah tantangan zaman yang cepat penuh dengan kecanggihan teknologi yang modern. Implikasi praktis dan teoritis dari temuan ini dibahas, serta rekomendasi untuk pengembangan pendidikan agama Kristen yang lebih adaptif terhadap realitas ruang virtual yang semakin kompleks.